Synthesis of Ag3VO4 nanoparticles loaded on Bi2MoO6 nanoplates as heterostructure visible light driven photocatalyst by sonochemical method - Nualkaew P. (2017)
©2016 The Ceramic Society of Japan. All rights reserved. Ag 3 VO 4 /Bi 2 MoO 6 nanocomposites were successfully synthesized by sonochemical method. The as-synthesized products were characterized by X-ray powder diffraction (XRD), field emission scanning electron microscopy (FE-SEM), selected area electron diffraction (SAED), transmission electron microscopy (TEM) and high resolution transmission electron microscopy (HRTEM). The results revealed the formation of heterostructure Ag 3 VO 4 /Bi 2 MoO 6 nanocomposites. Photocatalytic activity of the nanocomposites was evaluated through the degradation of rhodamine B (RhB) dye under visible white light irradiation. Among them, heterostructure 10.0 wt% Ag 3 VO 4 /Bi 2 MoO 6 nanocomposites exhibited the highest photocatalytic activity up to 56.26% for the degradation of RhB dye under visible white light within 240 min.